Pengembangan Media Pembelajaran VIKEL (Video Animasi Edukasi Gunung Kelud) pada Materi Indonesia Kaya Budaya Siswa Kelas IV SD - Yani Ratna Sari; Novi Nitya Santi; Sutrisno Sahari (Lembaga Yasin AlSys, 2026)
Although the development of animated video-based learning media has been widely examined, the integration of Kediri local wisdom, particularly the legend of the origin of Mount Kelud, into Natural and Social Sciences (IPAS) learning media in the Merdeka Curriculum remains limited. This study aims to develop VIKEL (Gunung Kelud Educational Animated Video) media and to test its level of validity, practicality, and effectiveness in improving students’ learning outcomes on the material Indonesia Kaya Budaya. This study used a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects involved 33 fourth-grade students of Kayenlor State Elementary School, divided into a limited trial of 10 students and a large-scale trial of 23 students. Data were collected through observation, interviews, expert validation questionnaires, teacher and student response questionnaires, and pre-test and post-test questions, and were then analyzed descriptively and quantitatively using a percentage formula. The results showed that VIKEL media obtained a validity level of 92%, categorized as highly valid; a practicality level of 93.5%–96%, categorized as highly practical; and an effectiveness level indicated by an increase in the average pre-test to post-test scores from 40%–43% to 91%–92% and classical mastery of 90%–91%. These findings indicate that presenting local legends in the form of animated videos can improve students’ understanding and learning outcomes regarding cultural diversity material. This study contributes to the development of local wisdom-based IPAS learning media and strengthens the relevance of the ADDIE model in producing contextual, engaging, and elementary school learning needs-oriented teaching materials. The practical implications of this study provide an alternative medium for teachers to integrate regional folklore into formal learning while supporting the preservation of local culture. Further research can be directed toward testing the long-term impact of VIKEL media on students’ affective aspects and developing similar media based on local wisdom from other regions.